What Causes the Most Stress in Breast Radiology Practice? A Survey of Members of the Society of Breast Imaging. Issue 3 (19th April 2021) - Parikh, Jay R; Sun, Jia; Mainiero, Martha B
Abstract: Objective: The objective of this study is to determine the major stressors affecting practicing breast radiologists. Methods: All members of the Society of Breast Imaging within the United States received an email invitation to complete an anonymous survey evaluating stressors that may contribute to physician burnout. Stressors evaluated included pace at work, work–life balance, care of dependents, job security, financial strain, decreasing reimbursement, new regulations, delivering bad news, fear of getting sued, and dealing with difficult patients, radiologists, and administrators. Results: The overall response rate was 13.5% (312/2308). For those who opened the email, response rate was 24.6% (312/1269). The most prevalent stressors reported were working too fast (222/312, 71.2%), balancing demands of work with personal life (209/312, 70.0%), fear of getting sued (164/312, 52.6%), and dealing with difficult administrators (156/312, 50%). Prevalence of stress related to new regulation requirements, job security, financial strain, decreased reimbursement, dependent care, call, delivering bad news, and dealing with difficult patients, difficult referrers, and difficult radiologists were present in fewer than 50% of respondents. Conclusion: The most prevalent sources of stress in breast imaging radiologists relate to working too fast and balancing demands of work with time needed for personal life.